Development of Interaction Value in Boranan Dance as a Method to Reduce Academic Procrastination of Mahasantri - Iqnata, Ilma Tanzihan; Isriyah, Mudafiatun; Rahmawati, Weni Kurnia (Konseling Edukasi : Journal of Guidance and Counseling, 2025)
Development of Interaction Value in Boranan Dance as a Method to Reduce Academic Procrastination of Mahasantri.This study aims to develop and test the effectiveness of an educational counseling module based on Boranan dance values in reducing academic procrastination behavior among PPA Ibnu Katsir Jember students. The background of this study is based on the high number of academic procrastination which has an impact on decreasing achievement and learning motivation. This study uses the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model to produce a valid, applicable, and contextual module product. Validation was carried out by guidance and counseling material experts, while the module trial was carried out through three group counseling sessions with 31 students. The validation results showed that the module scored 80%, was valid and feasible to use with minor revisions. The implementation of the module showed a decrease in procrastination behavior from 83% to 57%, proving the effectiveness of the local culture-based approach. The implications of this study indicate that educational counseling that integrates local wisdom values, such as persistence in the Boranan dance, is not only effective psychopedagogically, but is also able to strengthen the cultural identity of students within the framework of character education. It is recommended that this module be adapted and applied more widely in various Islamic boarding school-based educational institutions or other cultural localities as an alternative contextual and transformative intervention.Keywords: Interaction Value, Academic Procrastination; Boranan Dance